The Principals’s Program in Increasing the Professional Competence of Teachers in the TK Pelangi Bahayangkara Medan - Grace Marlina Tanjung; Dorlince Simatupang (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to describe the principal’s program in increasing teacher professional competence, teacher professional competence as well barriers to school printicipals in improving the professional competence of teacher TK Pelangi Bhayangkara Medan. The research method used in this study is a qualitative method using data collection techniques through observation, interviews and analysis. The subjects of this study were the principal and 4 (four) teachers of TK Pelangi Bhayangkara Medan. Data analysis techniques in this study used the Miles and Huberman models, namely data collection, data reduction, data presentation and verification and confirmation of conclusions. The research finings show that the school principals implement various programs with the aim of increasing teacher ptofesisional competence which include the Kelompok Kerja Guru (KKG), Penilaian Kinerja Guru (PKG), Sertifikasi, Pendidikan and Pelatihan (Diklat). The teacher’s efforts to increase teachers professional competence are by participating in various seminars, webinars, discussion with colleagues and attending training. Based on the research results, it is known that school principals always support teachers to increase professional competence through the role of school principals and participate in various other activities that can assist in improving teacher professional competence.